Aplicación de las medidas socioeducativas privativas de libertad de los adolescentes infractores - Reyna Rugel, María Salomé (2015)
This thesis on the theme: "Legal analysis of the implementation of custodial educational measures for young offenders freedom of the Code of Childhood and Adolescence", consists of six chapters which describe relevant aspects on the subject investigated. In the introduction a legal analysis of the implementation of custodial educational measures of freedom of juvenile offenders is done, the problem areas are identified, the justification, the general objective and specific, the hypothesis, the independent variables, dependent and described human, material and budget: resources are detailed. The theoretical framework consists of background research, foundation, doctrine, jurisprudence, law and comparative law in relation to the subject matter of this investigation that is a legal analysis of the implementation of educational measures deprivation of liberty of juvenile offenders. In the methodology, the methods used are detailed, the skills involved in field work, interviews with citizens of Canton Quevedo, and interview different professionals of this medium, data were analyzed interpreted tabulated, and then formulate the report of the investigation and verification of the hypothesis. Conclusions and Recommendations. By last. legal reform proposal is made to Art. 379 of the Code of Childhood and Adolescence, bibliography and detailed annexes.